2018
DOI: 10.1002/pola.29272
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple hydrogen bonding containing supramolecular thermoplastic elastomers: Mechanical and morphological correlations

Abstract: We report the design of bioinspired, reversible supramolecular thermoplastic elastomers (TPEs) functionalized with ureido‐cytosine (UCyt) complementary quadruple hydrogen bonding (QHB) sites. The polymer contained a soft poly(n‐butyl acrylate) central block that imparted flexibility and two external, hard nucleobase‐containing blocks that contributed to structural integrity. In addition, the hard block with pendant QHB motifs served as efficient physical crosslinks to further enhance the thermomechanical perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 43 publications
(63 reference statements)
4
27
0
Order By: Relevance
“…On the contrary, the hard domains were composed of mostly UCyA that enabled the formation of densely packed crosslinks, thus dissociated at higher temperatures. Similarly, Long et al observed an increasing terminal flow temperature when hydrogen bonding unit increased in the copolymer [21]. Additionally, all UCyA copolymers flowed at~150 • C, suggesting minor effects of the central block on the terminal flow temperature.…”
Section: Thermomechanical Analysismentioning
confidence: 64%
See 4 more Smart Citations
“…On the contrary, the hard domains were composed of mostly UCyA that enabled the formation of densely packed crosslinks, thus dissociated at higher temperatures. Similarly, Long et al observed an increasing terminal flow temperature when hydrogen bonding unit increased in the copolymer [21]. Additionally, all UCyA copolymers flowed at~150 • C, suggesting minor effects of the central block on the terminal flow temperature.…”
Section: Thermomechanical Analysismentioning
confidence: 64%
“…An additional higher temperature transition step at~85 • C was associated with the external blocks. It is noteworthy that the T g of the CyA external block was slightly lower compared with the T g of a poly(CyA) homopolymer (~93 • C) [21], indicative of phase mixing that originated from interactions among the CyA units between the central and external blocks. Figure 3B depicts the thermal transition profiles of UCyA copolymers.…”
Section: Thermal Analysismentioning
confidence: 93%
See 3 more Smart Citations